Air and gas drilling manual : applications for oil, gas, geothermal fluid recovery wells, specialized construction boreholes, and the history and advent of the directional DTH. - Lyons, William C.; Stanley, James H.; Sinisterra, Francisco J.; Weller, Tom (Gulf Professional Publishing, 2020)
Air and Gas Drilling Manual, Fourth Edition: Applications for Oil, Gas and Geothermal Fluid Recovery Wells, and Specialized Construction Boreholes, and the History and Advent of the Directional DTH delivers the fundamentals and current methods needed for engineers and managers engaged in drilling operations. Packed with updates, this reference discusses the engineering modelling and planning aspects of underbalanced drilling, the impacts of technological advances in high angle and horizontal drilling, and the importance of new production from shale. in addition, an in-depth discussion is included on well control model planning considerations for completions, along with detailed calculation examples using Mathcad. This book will update the petroleum and drilling engineer with a much-needed reference to stay on top of drilling methods and new applications in today's operations.
Previous edition: 2009.
Keywords: Air drilling (Petroleum engineering); Gas drilling (Petroleum engineering); elektronické knihy; electronic books